Effect of road pavement defects on tyre-road noise - Freitas, E. F. (2019)
Tyre-road noise is the main source of noise in vehicles at speeds above 40 km/h and therefore a major contributor to noise annoyance. As the road surface is submitted to traffic loading and weather, its characteristics change, and different types of distresses become visible on the surface, affecting the tire-road noise. This study aimed at analysing the tyre-road noise measured in different types of road pavements through acoustic and psychoacoustic indicators. The close proximity method (CPX) was used to measure noise at three speed levels (30km/h, 50 km/h and 65 km/h), in three types of road pavements, over two types of distresses (alligator cracking and ravelling). The effects of type of pavement, speed and distress on each acoustic and psychoacoustic indicator were analysed. It was confirmed that the pathologies have a relevant contribution to the tire-road noise. Also, the psychoacoustic indicators are more sensitive to the testing conditions. These results are a valuable argument to compel road managers to practice a preventive road maintenance policy.